The Natural History of Chronic Airflow Obstruction Revisited: An Analysis of the Framingham Offspring Cohort - Kohansal, Robab; Martinez-Camblor, Pablo; Agusti, Alvar; Buist, A. Sonia; Mannino, David M; Soriano, Joan B (American journal of respiratory and critical care medicine, 2009)
Understanding normal lung development and aging in health and disease, both in men and in women, is essential to interpreting any therapeutic intervention. We aimed to describe lung function changes in healthy never-smoking males and females, from adolescence to old age, and to determine the effects of smoking and those derived from quitting. Prospective cohort study within all participants of the Framingham Offspring cohort who had two or more valid spirometry measurements during follow-up (n = 4,391; age range at baseline 13 to 71 yr), with a median follow-up time of 23 years. To best fit the curves describing FEV(1) changes with age to raw data, we used a generalized additive model with smooth terms and incorporating the subject-specific (longitudinal) random effects. We found that: (1) healthy never-smoker females achieve full lung growth earlier than males, and their rate of decline with age was slightly, but not significantly, lower; (2) smoking increases the rate of lung function decline, both in males and in females; (3) there is a range of susceptibility to the effects of smoking. The presence of respiratory symptoms at baseline and/or a respiratory diagnosis during follow-up appears to identify a group of susceptible smokers; and (4) quitting smoking has a beneficial effect at any age, but it is more pronounced in earlier quitters. Lung function changes from adolescence to old age differ in males and females, smoking has similar deleterious effects in both sexes, and quitting earlier is better.